2019
DOI: 10.5433/1679-0359.2019v40n6supl2p3007
|View full text |Cite
|
Sign up to set email alerts
|

Tillage systems and nitrogen timings effect on growth, stay green and grain quality in maize (Zea mays L.)

Abstract: Nitrogen (N), being mobile in soil is exposed to various losses owing to unwise use of nitrogen fertilizer, and conventional soil and crop management practices which can be minimized by temporal nitrogen application and different tillage practices. This study was conducted to elucidate the effect of different tillage systems and nitrogen timings on growth, stay green and grain quality in maize. Three tillage systems viz. T1: tillage with cultivator, T2: mouldboard plough + 2-cultivations, T3: chisel plough + 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The highest starch content observed under SN6 was perhaps due to the possibility that the postponement of fertilization favored grain filling and amyloplastic development, as reported in rice. 13 Studies on the effects of different application times of traditional fertilizers also reported that postponing N application increases the starch content in normal maize 5 and rice. 14 Relative to the NCK mode, treatments SN3 and SN6 produced similar starch contents.…”
Section: Grain Starch Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest starch content observed under SN6 was perhaps due to the possibility that the postponement of fertilization favored grain filling and amyloplastic development, as reported in rice. 13 Studies on the effects of different application times of traditional fertilizers also reported that postponing N application increases the starch content in normal maize 5 and rice. 14 Relative to the NCK mode, treatments SN3 and SN6 produced similar starch contents.…”
Section: Grain Starch Contentmentioning
confidence: 99%
“…High N application rates decrease grain breakage susceptibility and increase grind time and hard endosperm percentage 3 . Split N application times can increase grain yield and protein content, 4 and postponing N application to the tasseling stage can improve grain quality by increasing starch and protein contents 5 . In rice, N application can enhance gelatinization parameters by improving protein content, 6 increasing starch pasting temperature and final and setback viscosities, and decreasing peak and breakdown viscosities 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation